2016
DOI: 10.1155/2016/9416908
|View full text |Cite
|
Sign up to set email alerts
|

Standard versus Abdominal Lifting and Compression CPR

Abstract: Background. This study compared outcomes of abdominal lifting and compression cardiopulmonary resuscitation (ALP-CPR) with standard CPR (STD-CPR). Materials and Methods. Patients with cardiac arrest seen from April to December 2014 were randomized to receive standard CPR or ALP-CPR performed with a novel abdominal lifting/compression device. The primary outcome was return of spontaneous circulation (ROSC). Results. Patients were randomized to receive ALP-CPR (n = 40) and STD-CPR (n = 43), and the groups had si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 22 publications
0
23
1
7
Order By: Relevance
“…Previous studies have shown that compared with AACD-CPR, STD-CPR can provide higher MAP [22]. In this study, although MAP of STD-CPR group was slightly higher, but the AACD-CPR group in CaO2, DO2, pH value.…”
Section: Discussioncontrasting
confidence: 54%
“…Previous studies have shown that compared with AACD-CPR, STD-CPR can provide higher MAP [22]. In this study, although MAP of STD-CPR group was slightly higher, but the AACD-CPR group in CaO2, DO2, pH value.…”
Section: Discussioncontrasting
confidence: 54%
“…[22] , and the pressure was set at 12cmH 2 O (model: PG120, Aesculap Inc., Tuttlingen, Germany). Abdominal wall lifting and compression [23] was performed at a frequency of 60bpm, a ratio of 1:1, and a strength of 50N. Arterial blood gas (ABG) analyses were performed at baseline and at 6, 7, 8, 9, and 10 minutes, respectively, after the endotracheal tube was clamped, as well as at the time of asphyxia termination(model: GEM Premier 3000, Instrumentation Laboratory, Lexington, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Z α / 2 and Z β are the upper (α /2)th and βth percentiles of the standard normal distribution, respectively. In another similar research, Sisen Zhang et al calculated the minimum sample size with a p t value of 0.21 and a p c value of 0.48 [12] . In our study, we determined the expected difference in not only the proportion of return of spontaneous circulation rate, but also the neurological function and the survival between two groups in the sample size estimation.…”
Section: Sample Sizementioning
confidence: 99%
“…All methods were carried out following relevant regulations and guidelines. The effectiveness, safety, and stability of the abdominal compression-decompression device used in this study have been veri ed in human experiments [11,12] .…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation